2019
DOI: 10.1136/bcr-2019-230567
|View full text |Cite
|
Sign up to set email alerts
|

Caecal duplication cyst leading to intussusception in an adult

Abstract: Colonic duplication cyst is an uncommon cause of intussusception in adults. We report a case of caecal duplication cyst in a 24-year-old adult with a 3-year history of recurrent abdominal pain mainly in the periumbilical region. CT and MRI of the abdomen showed a lesion suggesting an caecal duplication cyst within an intussuception. The patient underwent diagnostic laparoscopy and was found to have a caecal duplication cyst acting as a lead point for the intusseception for which laparoscopic-assisted resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We thus judged the lead point to be the cecum. In adults, cecal intussusception based on cecal cancer (9), lipoma (10), mobile cecum (11), and double intestinal tract (12) has been reported; however, no such findings have been reported so far in children. Such a discordant result might be partly attributed to the fact that endoscopy is rarely performed in children.…”
Section: Discussionmentioning
confidence: 99%
“…We thus judged the lead point to be the cecum. In adults, cecal intussusception based on cecal cancer (9), lipoma (10), mobile cecum (11), and double intestinal tract (12) has been reported; however, no such findings have been reported so far in children. Such a discordant result might be partly attributed to the fact that endoscopy is rarely performed in children.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic duplication is very rarely observed in adulthood [ 3 ]. With an estimated incidence of alimentary tract duplication of 1/10000 live births [ 1 , 2 ], 80% of the cases are discovered in the first two years of life [ 3 ]. Therefore, it is not surprising that surgeons may not encounter even a single adult case in their career.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al first reported in 2014, a case of 19-year-old patient with an ileocolic intussusception from an ileal duplication in an adult [ 11 ]. However, the first well-described case involving specifically a cecal duplication cyst leading to intussusception in a 24-year-old patient was published by Al-Shaibi et al [ 3 ]. A second case with a cecal duplication cyst, which occurred in a 63-year-old patient, was recently published, but the authors suggested that the intussusception was triggered by COVID-19 infection [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations